Criminal Responsibility of Children as Perpetrators of Murder - Yasmirah Mandasari Saragih; Rahul Ardian Fikri; Nabilah Syaharani (International Forum of Researchers and Lecturers, 2024)
Violent theft is indeed a crime that makes society restless. People dare to do it because of weak economic factors and always expect wealth that takes the property of others. The phenomenon that has occurred in society lately is that many perpetrators of violent theft are minors. This study aims to determine, examine and analyze 1. The Criminal Act of Violent Theft in Positive Law, 2. The Purpose of the Juvenile Criminal Justice System Based on Several Paradigms (Individual Guidance, Restorative Paradigm, and Distributive), According to the Beijing Rules, and the Children's Convention. The approach method used in this study is normative juridical. The specification of this study is descriptive analytical, the data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it can be concluded: 1. The crime of aggravated theft or theft with violence regulated in Article 365 is also a theft with qualifications or is a theft with aggravating elements. Thus, what is regulated in this article is actually only one crime, and not two crimes consisting of the crime of 'theft' and the crime of 'using violence against people'. 2. The juvenile justice system will prioritize the welfare of children and will ensure that any reaction to juvenile lawbreakers will always be commensurate with the circumstances of both the lawbreakers and the lawbreakers.